Kids write! : fantasy & sci fi, mystery, autobiography, adventure & more! - Olien, Rebecca; Kline, Michael P. (Nashville, Tenn. : Williamson Books, 2005)
From writing a script for a puppet show to designing a treasure map, this helpful guide introduces various forms of writing and encourages children to attempt to try their hand at creating original work of their own through activities, suggestions, and fun projects. Simultaneous.
"A Williamson kids can! book."
Includes index.
9 - 12 years
Keywords: Language arts (Elementary); Language arts (Middle school); Creative writing (Elementary education); Creative writing (Middle school)